La organización de pescadores artesanales de puerto Bolívar, provincia de El Oro como estrategia direccionada a la comercialización del producto año 2014 - Capa de la Cruz, Yadira Mireilli (2014)
The research study corresponds to the related Governmental Organizations that make the Organization of Fishermen of Puerto Bolivar, legal leaders of Fishermen's Associations and Ministries of the Organization of Fishermen, to determine a variety of problems seen facing fishermen in question.